-2(2m-3)+5(m+7)=40

Simple and best practice solution for -2(2m-3)+5(m+7)=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2m-3)+5(m+7)=40 equation:


Simplifying
-2(2m + -3) + 5(m + 7) = 40

Reorder the terms:
-2(-3 + 2m) + 5(m + 7) = 40
(-3 * -2 + 2m * -2) + 5(m + 7) = 40
(6 + -4m) + 5(m + 7) = 40

Reorder the terms:
6 + -4m + 5(7 + m) = 40
6 + -4m + (7 * 5 + m * 5) = 40
6 + -4m + (35 + 5m) = 40

Reorder the terms:
6 + 35 + -4m + 5m = 40

Combine like terms: 6 + 35 = 41
41 + -4m + 5m = 40

Combine like terms: -4m + 5m = 1m
41 + 1m = 40

Solving
41 + 1m = 40

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-41' to each side of the equation.
41 + -41 + 1m = 40 + -41

Combine like terms: 41 + -41 = 0
0 + 1m = 40 + -41
1m = 40 + -41

Combine like terms: 40 + -41 = -1
1m = -1

Divide each side by '1'.
m = -1

Simplifying
m = -1

See similar equations:

| 3(2x-4)-(x-3)=7(x+2)-1 | | 5(3x-1)+12=4(2x+3)+9 | | x-8=-3x+8 | | 4-2.50x=21.50 | | 2(x-3)+3(x+2)=10 | | -63=-(18+9x) | | x+4/3-2=10 | | 6x-4(5x+9)=4(2x+3)+9 | | 5(3x-4)=-14-3(x-10) | | (8n-5)(n+4)=0 | | 4-2(2x-7)=-6 | | 6x^2+78x+252=0 | | 6x+1-3=12x-(8x-4) | | -56+-1x+x^2=0 | | 6y^2+29y=22 | | (z+7)(z-8)=0 | | 4x^2-64x-68=0 | | 2(3+2x)-2=20 | | 24y-14y=5 | | 4z-3(2+1)=2(z-3)-z | | (x-4)(x-6)=-21 | | -13+(-4)(-2)= | | w^2-8w=20 | | 29x^2-7=0 | | .02(2c-24)=-0.4(c-1) | | 5a+3(8-a)=36 | | -97=-6x+11 | | (x+4)(x+6)+21=0 | | (x+4)(x+6)=-21 | | x+2=3-2x+8 | | -4c+4+2c=3c-16 | | 10x^2-3x-13=0 |

Equations solver categories